THE EFFECT OF ACCLIMATIZATION ON THE HEART RATE TO INCREASED ALTITUDE - Blaž Jereb; Stojan Burnik (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The aim of the present study is to monitor heart rate (HR) at real and at simulated altitude before and immediately after acclimatization, and one month after acclimatization. Six students of Faculty of Sport in Ljubljana (two women and four men) participated in the study. They undergone 18-day long acclimatization process on 2100 - 5642 m. HR was measured during the step test at 300 m, 2100 m, and 3800 m (in a laboratory »Josef Stefan« Ljubljana, at simulated altitude). The results show that the HR decreased significant immediately after acclimatization comparing to the values before acclimatization. HR values returned to the values before acclimatization one month after acclimatization.